Subclinical cardiomyopathy in Becker muscular dystrophy. Issue 9 (September 1992) - Steare, Stephen E; Dubowitz, Victor; Benatar, Avram
Abstract : Objective —To investigate the prevalence, age distribution, and spectrum of cardiac involvement in a cohort of patients with Becker muscular dystrophy. Design —A prospective non-invasive study with clinical, electrocardiographic, and echocardiographic assessment. Patients —19 patients (age range 16–41 years) with Becker muscular dystrophy attending the Muscle Clinic at Hammersmith Hospital and 22 healthy controls (age range 22–36 years). Results —17 patients (89%) were symptom free; two had exertional dyspnoea. Three had a past history of acute pericarditis. The electrocardiogram was abnormal in 14 patients (74%). Intraventricular conduction delay or right bundle branch block was present in eight (42%). Three (16%) had tall R waves (R/S > 1) in lead V1 in the absence of right bundle branch block and eight (42%) had Q waves in the lateral and inferolateral leads. The PQ interval was significantly shorter in patients with Becker muscular dystrophy (p < 0·01). Echocardiography showed left ventricular dilatation in seven patients (37%) and 12 (63%) had subnormal systolic function caused by global hypokinesia (fractional shortening <27%). Six of these patients were under the age of 22 years. Patients with Becker muscular dystrophy had significant reduction of both fractional shortening and corrected mean velocity of circumferential shortening compared with controls. No correlation was found between fractional shortening and age. The third filling fraction was significantly reduced in patients with Becker muscular dystrophy (p < 0·05), although other indices of diastolic function (isovolumic relaxation time and E/A ratios) were not significantly different. Conclusions —Though most patients with Becker muscular dystrophy were symptom free, a high percentage had evidence of a subclinical cardiomyopathy. Electrocardiography showed that the inferolateral and posterior segments of the left ventricle tended to be affected and may show evidence for conduction tissue disease. Echocardiography showed that most patients had left ventricular dilation and global hypokinesia. The severity of left ventricular disease was unrelated to age; some younger patients had severe left ventricular dysfunction. All patients with Becker muscular dystrophy should have echocardiographic assessment of left ventricular function.